Prophylactic Cavotricuspid Isthmus Ablation in Atrial Fibrillation without Documented Typical Atrial Flutter: A Systematic Review and Meta-analysis. Issue 1 (2022) - Waranugraha, Yoga; Rizal, Ardian; Rohman, Mohammad Saifur; Tsai, Chia-Ti; Chiu, Fu-Chun
No abstract available